Step 1: Determine the conjugate of the denominator. ( to find the conjugate just change the sign of the imaginary part ).
In this example, the conjugate of $ \color{orangered}{ 2+i }\, $ is $ \color{blue}{ 2-i } $.
Step 2: Multiply both the numerator and denominator by the conjugate:
$$\begin{aligned} \frac{ 1+i }{ 2+i } &= \frac{ 1+i }{ 2+i } \cdot \frac{ \color{blue}{ 2-i } }{ \color{blue}{ 2-i } } = \\[1 em] &= \frac{ \left( 1+i \right) \cdot \left( 2-i \right) }{ \left( 2+i \right) \cdot \left( 2-i \right) } \end{aligned} $$Step 3: Simplify numerator and denominator (use $\color{blue}{i^2 = -1}$)
$$ \begin{aligned} \left( 1+i \right) \cdot \left( 2-i \right) &= 1 \cdot 2 + 1 \cdot \left(-1 \,i \right) + \left( 1 \,i \right) \cdot \left(2 \right) + \left( 1 \,i \right) \cdot \left(-1 \,i \right) = \\[1 em] &= 2 -1 \, i + 2 \, i -1 \color{blue}{(-1)} = \\[1 em] &= 3+i\end{aligned} $$ $$ \begin{aligned} \left( 2+i \right) \cdot \left( 2-i \right) &= 2 \cdot 2 + 2 \cdot \left(-1 \,i \right) + \left( 1 \,i \right) \cdot \left(2 \right) + \left( 1 \,i \right) \cdot \left(-1 \,i \right) = \\[1 em] &= 4 -2 \, i + 2 \, i -1 \color{blue}{(-1)} = \\[1 em] &= 5\end{aligned} $$Step 4: Separate real and imaginary parts:
$$ \frac{ 1+i }{ 2+i } = \frac{ 3+i }{ 5 } = \frac{ 3 }{ 5 } + \frac{ 1 }{ 5 } i= \frac{ 3 }{ 5 }+\frac{ 1 }{ 5 }i $$